TRANSFORMASI NILAI KEARIFAN LOKAL DALAM MEMPERKOKOH KARAKTER BANGSA : Studi Kasus Tentang Budaya Siri'na Pacce di Universitas Negeri Makassar - Muhammad Amin, - (2017)
This research background was by the emerged of worries about the faded of cultural values among the public, the negative impact of globalization, and other social symptoms. There was other alternative solutions offered namely the necessity of transforming local wisdom value in order to strengthen the character of the nation. This research was used qualitative approach with case study design. Technique of collecting data were interview, observation, and documentation. The research data was analyzed through the process of reduction, presentation, withdrawal conclusions/ data verification. The research finding showed that (1) transformation of cultural value siri'na pacce within the scope of State University of Makassar have implications for negative and positive. As for the positive implications, it can be used for one of sources that strengthening students' character, such us high achieving students, discipline, responsible, respecting-valuing each other, solidarity and those social care character were realized through adapting students' attitude and behavior; (2) the implications of cultural values siri'na pacce that have transformed toward the building of the national character was evolutive; and (3) the transformation of cultural value siri'na pacce was believed to be relevant with the mission of the civic education in socio-cultural dimension namely characters which accompanied by the commitment of the citizens who always glorify and honor the human dignity, where it believed to be the virtue of the citizen.---- Penelitian dilatarbelakangi oleh munculnya kekhawatiran tentang lunturnya aktualisasi nilai-nilai budaya dikalangan masyarakat, dampak negatif globalisasi, dan gejala sosial lainnya. Adapun alternatif solusi yang ditawarkan yakni perlunya tranformasi nilai kearifan lokal guna memperkokoh karakter bangsa. Penelitian ini menggunakan pendekatan kualitatif dengan desain studi kasus. Teknik Pengumpulan data yang digunakan yakni wawancara, observasi dan studi dokumentasi. Data penelitian dianalisis melalui proses reduksi, penyajian dan penarikan kesimpulan/verifikasi data. Simpulan temuan penelitian: (1) Transformasi nilai budaya siri' na pacce dalam lingkup Universitas Negeri Makassar berimplikasi negatif dan positif. Adapun implikasi positifnya dapat dijadikan sebagai salah satu sumber nilai guna penguatan karakter mahasiswa, seperti berprestasi, kedisiplinan, bertanggungjawab, saling menghargai-menghormati, solidaritas dan kepedulian sosial. Karakter tersebut diwujudkan melalui pembiasan sikap dan perilaku mahasiswa; (2) Implikasi nilai budaya siri' na pacce yang telah bertransformasi terhadap pembangunan karakter bangsa bersifat evolutif; dan (3) Transformasi nilai budaya siri' na pacce diyakini relevan dengan misi pendidikan kewarganegaraan dalam dimensi sosio-kultural yakni karakter disertai komitmen warga negara yang senantiasa memuliakan dan menghormati harkat dan martabat kemanusiaan, diyakini sebagai kebajikan warga negara.